The catalytic mechanism of the 3-ketosteroid isomerase of Digitalis lanata involves an intramolecular proton transfer and the activity is not associated with the 3β-hydroxysteroid dehydrogenase activity. Issue 14 (6th April 2016) - Meitinger, Nadine; Munkert, Jennifer; Maia de Pádua, Rodrigo; de Souza Filho, José Dias; Maid, Harald; Bauer, Walter; Braga, Fernão Castro; Kreis, Wolfgang
Graphical abstract: Highlights: Reaction mechanism of Digitalis lanata 3KSI is investigated. Isoprogesterone isomerization proceeds via an intramolecular proton transfer. The mechanism is consistent with the mechanism of the bacterial 3KSIs. r Dl 3βHSD does not possess 3-ketosteroid isomerase activity. Abstract: The isomerization of the Δ 5 -3-ketosteroid isoprogesterone into the Δ 4 -3-ketosteroid progesterone has been examined with recombinant 3β-hydroxysteroid dehydrogenase from Digitalis lanata (r Dl 3βHSD), partially purified 3-ketosteroid isomerase from Digitalis lanata ( Dl 3KSI) and under non-enzymatic conditions in deuterium oxide (D2 O). Studies indicate that the isomerization catalyzed by the Dl 3KSI proceeds without significant isotope exchange between the medium and the steroid and thus involves an intramolecular proton transfer consistent with the mechanism of the bacterial 3-ketosteroid isomerase of Pseudomonas testosteroni . For the r Dl 3βHSD as well as under non-enzymatic conditions deuterium was incorporated from the incubation buffer during isomerization. Together with a comparison of the rate of isomerization under the different conditions, it was demonstrated that r Dl 3βHSD does not possess 3-ketosteroid isomerase activity.